Juvenile hormone signaling promotes ovulation and maintains egg shape by inducing expression of extracellular matrix genes. - Luo, W.; Liu, S.; Zhang, W.; Yang, L.; Huang, J.; Zhou, S.; Feng, Q.; Palli, S.R.; Wang, J.; Roth, S.; Li, S. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
It is well documented that the juvenile hormone (JH) can function as a gonadotropic hormone that stimulates vitellogenesis by activating the production and uptake of vitellogenin in insects. Here, we describe a phenotype associated with mutations in the Drosophila JH receptor genes, Met and Gce: the accumulation of mature eggs with reduced egg length in the ovary. JH signaling is mainly activated in ovarian muscle cells and induces laminin gene expression in these cells. Meanwhile, JH signaling induces collagen IV gene expression in the adult fat body, from which collagen IV is secreted and deposited onto the ovarian muscles. Laminin locally and collagen IV remotely contribute to the assembly of ovarian muscle extracellular matrix (ECM); moreover, the ECM components are indispensable for ovarian muscle contraction. Furthermore, ovarian muscle contraction externally generates a mechanical force to promote ovulation and maintain egg shape. This work reveals an important mechanism for JH-regulated insect reproduction.